Kansas Field Research 2021 (Kansas Agricultural Experiment Station Research Reports, 2021)
A summary of research conducted in 2019-2020 on field production and management practices for crops in Kansas. Published in 2021 from the Kansas State University Agricultural Experiment Station and Cooperative Extension Service https://www.ag.k-state.edu/
Keywords: corn; tillage; sorghum; management practices; soybean; Kansas weather; weed science; wheat; planting dates; grain weight; tiller yield; vertical tillage; no-till; deep till; Field Scout TDR 300; grazing; cover crops; soil properties; soil evaporation; residue cover; AquaSpy soil moisture sensors; nitrogen management; forage accumulation; dryland; irrigation; smooth brome; kochia; fungicide management; flag leaf; seeding rate; seed cleaning